Malignant transformation in the course of a dentigerous cyst: a problem for a clinician and a pathologist. Considerations based on a case report - Zapała-Pośpiech, Agnieszka; Wyszyńska-Pawelec, Grażyna; Adamek, Dariusz; Tomaszewska, Romana; Zaleska, Małgorzata; Zapała, Jan (Polish Journal of Pathology, 2013)
Primary intraosseous squamous cell carcinoma (PIOSCC) is a rarely reported neoplasm resulting from malignant transformation of a dentigerous cyst of the mandible or maxilla. Until 2010, only 116 cases had been described. The diagnosis of PIOSCC is difficult because of non-specific symptoms. A case of a 66-year-old patient with PIOSCC arising from a dentigerous cyst of the mandible is presented. Both pathologists and clinicians should be aware of the probability of malignant transformation of dentigerous cysts during the two-stage treatment. The patient should be subject to regular clinical and radiographic examination.